Comparison of SPH and CEL methods for simulating the soil cutting process of a biomimetic digging shovel - Yunning Dong; Liangfei Fang; Kuan Qin; Shoujun Sun; Yue Gong (PLoS ONE, 2025)
Changes in the resistance of tillage tools during cultivation are often investigated through field tests to reduce carbon emissions from agricultural machinery during tillage. Tillage tools are optimized using the test results to minimize energy loss. However, field tests typically face challenges such as high experimental costs, soil and climate limitations, and operational complexity. Numerical simulation, as a computer-aided research method, offers several advantages, including ease of use, cost-effectiveness, and resource conservation. This study employed the smoothed particle hydrodynamics (SPH) method and the coupled Eulerian-Lagrangian (CEL) method to examine the interaction between a biomimetic digging shovel and soil. In parallel, soil bin experiments were conducted, and the simulation results were compared to experimental data. The findings revealed that the simulated changes in cutting resistance were consistent with the experimental results, confirming the reliability of both models. Simulation results indicated that the CEL model required 6 h and 35 min to compute, while the SPH model required 7 h and 18 min. The relative error between the CEL model and the soil bin experiment was 8.81%, while that between the SPH model and the experiment was 13.76%. These results highlight the superior computational efficiency and higher computational accuracy of the CEL model. The validated CEL model was subsequently used to simulate the interactions between the digging shovel and soil under varying conditions.